Hypoglycemic Effect of Zingiber Zerumbet Ethanolic Extracts and Channa Striata Powder in Alloxan-Induced Diabetic Rats - Muhtadi, M.; Annissa, Yanis Nur; Suhendi, Andi; Sutrisna, EM. (Universitas Muhammadiyah Surakarta, 2018)
The ethanolic extracts of the Zingiber zerumbet rhizome contains flavonoid and zerumbon compounds, the fish meat powder from Channa striata has an albumin content. The active compounds was contained in both materials had activity that can lower blood sugar levels in diabetic rats. This study aims to determine the hypoglycemic effect of each ingredients and the combination of Z. zerumbet rhizome extract and C. striata powder in alloxan-induced diabetic rats. This research uses pre and post test method with the control group design. The treatment was consisted of 5 groups, the first group was given aquades (as negative control), the second group was given glibenclamide with dose 5 mg/kgBW (as positive control), the third group was given 300 kg/kgBW of Z. zerumbet rhizome extract, the fourth group was given of C. striata fish powder 300 mg/kgBW, and the last group was given a combination materials with dosesrespectively, 300 mg/kgBW. The ingredient was given for 12 days and blood was taken on days 3, 6, and 12. The results shows the percentage of decrease in blood sugar of combination materials of 70.4% is greater than the single content of Z. zerumbet and C. striata, with the value of successive activity of 62.9% and 34.4%, respectively. The antidiabetic activity of combinations of materials had produced not different significant (p> 0.05) compared with single of C. striata powder as well as the Z. zerumbet rhizome extract.